Potret Relasi Suami-Istri Jamaah Mentaok Kotagede dalam Kajian Social Exchange - Mohammad Fauzan Ni'ami (State Islamic University (UIN) of Sunan Ampel, 2021)
This article aims to explore the portrait of the husband-wife relationship of the Yogyakarta Mentaok Congregation. The discussion is preceded by a study of husband and wife in the family, followed by a picture of the relationship pattern of the Mentaok Congregation Kotagede Yogyakarta, and then the shift in roles in the family of the Mentaok congregation in a social exchange review. The method used in this article is field research which is then analyzed deductively using a social exchange approach. The results of this study illustrate at least three patterns of relations between the Mentaok congregation: first, husband and wife work, and the wife takes care of domestic work. Second, the husband and wife work while other people care for their household work. The third form is husband and wife work, and both plunge into the domestic sphere. In a review of social exchange, researchers found that there is reciprocity in the family of the Yogyakarta Kotagege Mentaok Congregation, which is mutually beneficial and, at the same time, demands a sacrifice for a family.